A prospective newborn screening and treatment program for sickle cell anemia in Luanda, Angola. Issue 12 (15th October 2013) - McGann, Patrick T.; Ferris, Margaret G.; Ramamurthy, Uma; Santos, Brigida; de, Vysolela; Bernardino, Luis; Ware, Russell E.
<x xml:space="preserve">Abstract</x> Over 300, 000 infants are born annually with sickle cell anemia (SCA) in sub‐Saharan Africa, and >50% die young from infection or anemia, usually without diagnosis of SCA. Early identification by newborn screening (NBS), followed by simple interventions dramatically reduced the mortality of SCA in the United States, but this strategy is not yet established in Africa. We designed and implemented a proof‐of‐principle NBS and treatment program for SCA in Angola, with focus on capacity building and local ownership. Dried bloodspots from newborns were collected from five birthing centers. Hemoglobin identification was performed using isoelectric focusing; samples with abnormal hemoglobin patterns were analyzed by capillary electrophoresis. Infants with abnormal FS or FSC patterns were enrolled in a newborn clinic to initiate penicillin prophylaxis and receive education, pneumococcal immunization, and insecticide‐treated bed nets. A total of 36, 453 infants were screened with 77.31% FA, 21.03% FAS, 1.51% FS, and 0.019% FSC. A majority (54.3%) of affected infants were successfully contacted and brought to clinical care. Compliance in the newborn clinic was excellent (96.6%). Calculated first‐year mortality rate for babies with SCA compares favorably to the national infant mortality rate (6.8 vs. 9.8%). The SCA burden is extremely high in Angola, but NBS is feasible. Capacity building and training provide local healthcare workers with skills needed for a functional screening program and clinic. Contact and retrieval of all affected SCA infants remains a challenge, but families are compliant with clinic appointments and treatment. Early mortality data suggest screening and early preventive care saves lives. Am. J. Hematol. 88:984–989, 2013. © 2013 Wiley Periodicals, Inc.